Modern Machining Technology - Advanced, Hybrid, Micro Machining and Super Finishing Technology - Bhattacharyya, Bijoy; Doloi, Biswanath (Elsevier, 2020)
This book explores complex and precise components with challenging shapes that are increasing in demand in industry. As the first book to cover all major technologies in this field, readers will find the latest technical developments and research in one place, allowing for easy comparison of specifications. Technologies covered include mechanical, thermal, chemical, micro and hybrid machining processes, as well as the latest advanced finishing technologies. Each topic is accompanied by a basic overview, examples of typical applications and studies of performance criteria. In addition, readers will find comparative advantages, model questions and solutions.